Keynote Address. Tales From the Field: Reflections on Four Decades of Ethnography - Adler, Patricia A.; Adler, Peter (Qualitative Sociology Review, 2012)
Drawing on careers spanning over 35 years in the field of ethnography, we reflect on the research in which we’ve engaged and how the practice and epistemology of ethnography has evolved over this period. We begin by addressing the problematic nature of ethical issues in conducting qualitative research, highlighting the non-uniform nature of standards, the difficulty of applying mainstream or medical criteria to field research, and the issues raised by the new area of cyber research, drawing particularly on our recent cyberethnography of self-injury. We then discuss the challenge of engagement, highlighting pulls that draw ethnographers between the ideals of involvement and objectivity. Finally, we address the challenges and changing landscapes of qualitative analysis, and how its practice and legitimation are impacted by contemporary trends in sociology. We conclude by discussing how epistemological decisions in the field of qualitative research are framed in political, ethical, and disciplinary struggles over disciplinary hegemony